The method of the fundamental solutions and its modifications for electromagnetic field problems - Chen, C. S.; Reutskiy, S. Y.; Rozov, V. Y. (Computer Assisted Methods in Engineering and Science, 2009)
The paper presents the method of fundamental solutions (MFS) for solving electromagnetic problems. We compare the MFS with the method of boundary integral equations in solution of potential problems. We demonstrate the MFS technique together with the Laplace transform in application to the problem of scattering of electromagnetic pulses. A modification of the MFS - the method of approximate fundamental solutions (MAFS) is also considered in the paper. The method is applied to axisymmetric field problems. Numerical examples justifying the methods are presented.